Etnopragmatik og interkulturel kompetence: Didaktiske nytænkninger i fremmedsprogsundervisningen - Fernández, Susana S. (Ny forskning i grammatik, 2016)
The purpose of this paper is to explore the possible pedagogical application of ethnopragmatics in the field of language learning and teaching with the purpose of promoting intercultural communicative competence. The ethnopragmatic approach, developed by Anna Wierzbicka, Cliff Goddard and associates within the broad paradigm of Cognitive Linguistics, examines cultural aspects of language and communication from an insider’s perspective. The pedagogical potential of ethnopragmatics lies in its effort for unravelling the values, beliefs and norms that lie behind the verbal behavior of a particular cultural group and in doing so without a predetermined cultural bias.